Severe rheumatoid valvular heart disease (2006)
Rheumatoid arthritis (RA) is a systemic inflammatory disease in which extra-articular involvement is not uncommon. Cardiac compromise may be frequent, although most often, it is clinically silent. Herein, two cases of RA-related endocarditis, one of which required valve replacement, are described. Etanercept was useful in controlling the articular and extra-articular RA compromise in both cases. © Clinical Rheumatology 2006.